A pH-Responsive System Based on Fluorescence Enhanced Gold Nanoparticles for Renal Targeting Drug Delivery and Fibrosis Therapy - Lai X (Dove Medical Press, 2020)
Xuandi Lai,1 Xinran Geng,2 Lishan Tan,1 Jianqiang Hu,2 Shubin Wang1 1Department of Oncology, Shenzhen Key Laboratory of Gastrointestinal Cancer Translational Research, Peking University Shenzhen Hospital, Shenzhen Peking University-the Hong Kong University of Science and Technology Medical Center, Shenzhen 518036, People’s Republic of China; 2Nanobiological Medicine Center, Key Laboratory of Fuel Cell Technology of Guangdong Province, School of Chemistry and Chemical Engineering, South China University of Technology, Guangzhou 510640, People’s Republic of ChinaCorrespondence: Jianqiang HuNanobiological Medicine Center, Key Laboratory of Fuel Cell Technology of Guangdong Province, School of Chemistry and Chemical Engineering, South China University of Technology, No. 381, Wushan Road, Tianhe District, Guangzhou 510640, People’s Republic of ChinaTel +86-186 6571 1833Email jqhusc@scut.edu.cnShubin WangDepartment of Oncology, Shenzhen Key Laboratory of Gastrointestinal Cancer Translational Research, Peking University Shenzhen Hospital, Shenzhen Peking University-the Hong Kong University of Science and Technology Medical Center, No. 1120, Lianhua Road, Futian District, Shenzhen 518036, People’s Republic of ChinaTel +86-755-83923333Fax +86-755-83061340Email wangshubin2013@163.comBackground: Stimuli-responsive gold nano-assemblies have attracted attention as drug delivery systems in the biomedical field. However, there are challenges achieving targeted delivery and controllable drug release for specific diseases.Materials and Methods: In this study, a glutathione (GSH)-modified fluorescent gold nanoparticle termed AuLA-GSH was prepared and a Co2+-induced self-assembly drug delivery platform termed AuLA-GSH-Co was constructed. Both the pH-responsive character and drug loading behavior of AuLA-GSH-Co were studied in vitro. Kidney-targeting capability was investigated in vitro and in vivo. Finally, the anti-fibrosis efficiency of AuLA-GSH-Co in a mouse model of unilateral ureteral obstruction (UUO) was explored.Results: AuLA-GSH-Co was sensitive to pH changes and released Co2+ in acidic conditions, allowing it to have controllable drug release abilities. AuLA-GSH-Co was found to improve cellular uptake of Co2+ ions compared to CoCl2 in vitro. AuLA-GSH exhibited specific renal targeting and prolonged renal retention time with low non-specific accumulation in vivo. Moreover, the anti-fibrosis efficiency of AuLA-GSH-Co was higher compared to CoCl2 in a mouse model of unilateral ureteral obstruction (UUO).Conclusion: AuLA-GSH-Co could greatly enhance drug delivery efficiency with renal targeting capability and obviously relieve renal fibrosis, providing a promising strategy for renal fibrosis therapy.Keywords: gold nanoparticles, self-assembly, pH sensitivity, drug delivery, renal fibrosis